Gender Dysphoria in Minors: A Critical Look at Early Medicalization and Proposals for Ethical Support (Revista Iberoamericana de Bioética, 2025)
This article offers a critical analysis of the early medicalization of gender dysphoria in minors from a clinical and bioethical perspective. Beginning with an examination of the Dutch protocol, it explores the tensions between the affirmative model endorsed by WPATH and the recommendations of the British Cass Review. By examining the scientific and ethical foundations underpinning both approaches, the article underscores the inherent complexity of providing care to minors navigating identity-seeking processes.It also offers a bioethical reflection in which the vulnerability of minors is positioned as a guiding principle for deliberation. The article advocates for non-invasive, long-term clinical support and, ultimately, proposes a comprehensive model of care that prioritizes psychosocial assessment, psychological support, family involvement, and therapeutic prudence.
Keywords: gender dysphoria; childhood; bioethics; medicalization; evolving autonomy; clinical support